BUDIDAYA SAYURAN ORGANIK DENGAN POLYBAG UNTUK MENINGKATKAN KETAHANAN PANGAN DI DESA PEGUYANGAN KAJA, KECAMATAN DENPASAR UTARA - Ni Ketut Ayu Juliasih; Ni Wayan Merliana Dewi; Ni Luh Gede Suastini; I Dewa Gede Yoga Sedana (UNHI Press, 2021)
The 2021 Unhi KKN-PPM activity, in Peguyangan Kaja Village, Denpasar City, Bali Province was carried out for 5 weeks, (27 August to 30 September 2021). One of the KKN-PPM programs implemented is the food security program in the form of organic vegetable cultivation activities with polybags. This activity was adapted to the KKN-PPM theme that was carried, namely